O efeito da marca de luxo no bem-estar emocional e no apego ?? marca em contexos sociais estressantes - Silva, Leonardo Aureliano da (2015)
Studies with different perspectives have investigated the role of the brand in consumer behavior. Although there is an interface in the investigated constructs, still lacks depth in how the consumer attach to a brand to improve their emotional well-being in stressful social contexts. To better understand this issue a bibliographic research was performed and subsequently went on empirical research, which was conducted experiments with different brands and stress levels. The data obtained by sample of 365 individuals were compiled and analyzed by analysis of variance procedure. Analysis of the results of the experiments showed the following findings: a) in low stress scenario a luxury brand and a non-luxury brand had the same effect on the consumer??s emotional well-being and the level of attachment to the brand; in high-stress scenario the luxury brand compared to non-luxury brand influenced more positively consumer??s emotional well-being and the level of attachment to the brand.